BENEFITS OF BEE CULTIVATION - Н. А. Азизова; Х. О. Саноева (Web of Journals Publishing, 2025)
In the conditions of Bukhara region, the increase in the weight of eggs laid by queens due to additional feeding of bee families for artificial breeding of queens from the bee family of the local population. The weight of a bee's egg is related to the quality of the queen's large number of eggs, the strength of the bee's family, the weight of the queen's bees, and the number of egg tubes in her ovary.
Keywords: Quality mother, pollen, egg tubes, wheat grass water, control group, experimental group, mother bees, mother bee breeding from bee eggs, breeding bee family, mother bee breeding from bee larvae, plastic cup, wing length, wing width, 3-tergit, 3-sternit.